Our People, Our Resources : Striving for a Peaceful and Plentiful Planet - Duchicela, Luis Felipe (World Bank, Washington, DC, 2015)
This report presents a brief discussion of indigenous peoples’ development as evidenced in a select number of case studies about World Bank financed projects that had a positive impact on indigenous peoples’ communities. The main objective of this study is to identify and document good practices and lessons learned that can be shared with World Bank staff, borrower governments, and Indigenous Peoples’ organizations to help improve the design and implementation of projects that trigger the World Bank’s Operational Policy on Indigenous Peoples and/or are primarily oriented toward the sustainable development of indigenous peoples. World Bank activities with regard to indigenous peoples have been primarily focused on applying OP 4.10 to ensure that indigenous peoples receive social and economic benefits that are culturally appropriate and gender and age inclusive, and to mitigate possible adverse impacts associated with Bank-financed projects. The policy itself encourages Bank engagement and financial support for a variety of initiatives that go beyond projects, engaging in broader dimensions of country relationships that improve the circumstances of indigenous peoples. As a result, the Bank increasingly addresses issues concerning indigenous peoples through: (1) country economic and sector work/analysis, (2) dialogue and technical assistance, and (3) capacity-building. This report is an initial attempt to document good practices and lessons learned through results with regard to indigenous peoples’ development. It is intended to support the ongoing engagement process with indigenous peoples and to inform the process of finding better ways to promote sustainable development that will positively affect indigenous communities.